Discourses on gender and sexual inequality : the legacy of Sandra L. Bem - Kohlman, Marla H.; Krieg, Dana B. (Emerald Publishing Limited, 2017)
This edited collection examines the significance of Sandra L. Bem's research for current debates on gender and gender roles in the social sciences, with contributions that question how the institution of gender has been, and remains, deeply contested.
Preliminary Analyses.
Keywords: Bem, Sandra L.; Bem, Sandra L. -- Lenses of gender.; Sex role.; Sex discrimination.; elektronické knihy; electronic books